Primary Hepatic Leiomyosarcoma - A Rare Neoplasm with Diagnostic and Therapeutic Challenges - Gentile, João Kleber de Almeida; Renesto, Beatriz Terezinha Franco; Quintela, Eloíza Helena Dias; Bezerra, Alexandre Sacchetti; Magella, Flavia; Miléo, Luís Fernando Alves; Silva, Daniel de Castilho da; Souza Filho, Ronaldo Modesto de; Oliveira, André Cosme (Brazilian Journal of Case Reports, 2025)
Primary hepatic leiomyosarcoma (PHL) is a rare malignant neoplasm, representing <0.1% of all primary liver tumors. Originating from the smooth muscle cells of the intrahepatic vessels or the round ligament, its diagnosis is complex and requires the exclusion of metastases and other sarcomas. This case and literature review summarizes current knowledge on the epidemiology, clinical presentation, diagnostic approach and therapeutic management of LHP based on published literature. The clinical presentation is non-specific, often with abdominal pain and a detectable mass. Radical surgical resection (R0) is the only potentially curative treatment, but the high rate of local and metastatic recurrence negatively impacts the prognosis. Chemotherapy and radiotherapy have a limited palliative or adjuvant role. Overall survival at 5 years is low (15-30%), emphasizing the need for early diagnosis and more effective multimodal therapeutic strategies. The clinical presentation is non-specific, often with abdominal pain and a detectable mass. Radical surgical resection (R0) is the only potentially curative treatment, but the high rate of local and metastatic recurrence negatively impacts the prognosis. Chemotherapy and radiotherapy have a limited palliative or adjuvant role. Overall survival at 5 years is low (15-30%), emphasizing the need for early diagnosis and more effective multimodal therapeutic strategies.